THE ROLE OF MODERN COMPUTER TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE IN THE DIAGNOSIS AND TREATMENT OF DENTAL DISEASES IN YOUNG CHILDREN (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article discusses the role of modern computer technologies and artificial intelligence systems in the early detection and treatment of dental diseases in young children. The main reason for this is often non-compliance with hygiene rules, poor nutrition, hereditary factors, low immunity and vitamin deficiency. In dentistry departments, the advantages of technologies such as digital X-rays, 3D tomography, intraoral scanners are convenient and easy, and they save time, while work is being done to improve the diagnosis, treatment planning and prevention processes using artificial intelligence. It is also noted that these methods increase the accuracy of diagnosis, reduce the human factor and facilitate the treatment process in children.